2020
DOI: 10.1002/etc.4650
|View full text |Cite
|
Sign up to set email alerts
|

Tritiated Water Exposure in Zebrafish (Danio rerio): Effects on the Early‐Life Stages

Abstract: Tritium, a radioactive isotope of hydrogen of natural and anthropogenic origin, is ubiquitously present in the environment. Effluents of nuclear centers of production are significant anthropogenic sources. With the upcoming project of thermonuclear fusion, tritium releases in the environment may increase. It is therefore important to characterize the ecological risk linked to tritium. The effects of tritiated water (HTO) were therefore studied in zebrafish larvae exposed for 10 d to different dose rates, 1.1 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Many studies report that chemical environmental pollutants can induce ROS production in fish cells (Garcia-Gomez et al, 2020). Gagnaire et al (2019) revealed that DNA damage and ROS production were caused by the exposure of tritiated water. Our previous studies also showed the increase of ROS in cells after exposed to nodularin and microcystins (Zhang et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report that chemical environmental pollutants can induce ROS production in fish cells (Garcia-Gomez et al, 2020). Gagnaire et al (2019) revealed that DNA damage and ROS production were caused by the exposure of tritiated water. Our previous studies also showed the increase of ROS in cells after exposed to nodularin and microcystins (Zhang et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of a large number of genes in the two biological processes of redox and lipid transport in GO analysis also indicates that the antioxidant system in zebrafish has been disorder. It has been reported that exposure to tritiated water will also increase the level of ROS in zebrafish larvae (Gagnaire et al, 2020). We speculate that in terms of oxidative stress, the combined effects of tritiated water and genistein on zebrafish embryos may be superimposed, which leads to excessively high active oxygen of zebrafish larvae, and the original balanced redox system in the body is disrupted, thus affecting the normal function of cells.…”
Section: Discussionmentioning
confidence: 81%
“…Some characteristics related to apoptosis and senescence ensued, such as cell cycle arrest, increased γ H2AX and IL-8 contents, as well as an increase in the proportion of positive cells stained with β -galactosidase (SA- β -gal) [ 14 , 24 ]. Second, as ionizing radiation, Tritium caused the radiolysis of water, which promoted the formation of ROS [ 36 ] to attack intracellular biological macromolecules such as DNA, protein and lipids, causing cell damage [ 37 ]. In addition, Li et al treated AHH-1-1 with 3.7 × 10 6 Bq/mL tritiated water, and only 72.1% of the cells survived [ 17 ].…”
Section: Discussionmentioning
confidence: 99%